PENINGKATAN KETERAMPILAN MENULIS TEKS ANEKDOT DENGAN MEDIA KARIKATUR - Nurnaningsih, Luluk Ayu (sarasvati, 2020)
This research is based on the problem of how to improve anecdote writing skills by using caricature image media in class X SMA Negeri 1 Batu Sopang? The purpose of this study is to improve anecdote writing skills by using caricature image media in class X SMA Negeri 1 Batu Sopang. This study uses action research in two cycles. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is class X students. The data obtained were in the form of questionnaire results, teaching and learning activity observation sheets and anecdotal text writing test questions. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle II, namely, cycle I (72%,) and cycle II (83.1). The conclusion of this study is that caricature media can improve anecdotal writing skills in Class X SMA N 1 Batu Sopang, and the use of caricature media can be used as an alternative to learning Indonesian